Prediksi Jumlah Pengangguran Terbuka di Indonesia menggunakan Metode Genetic-Based Backpropagation - Dyva Pandhu Adwandha; Dian Eka Ratnawati; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The number of open unemployment in Indonesia has increased and decreased every year. The factors that can make unemployment happens is the number of the labor force is not balanced to the available jobs. In addition, the weakening of labor absorption in some industrial sectors has also the cause of the increasing number of open unemployment in Indonesia. Predict the number of open unemployment, expected can help the government and related parties to take the appropriate policy to reduce the number of open unemployment in Indonesia. Genetic-based backpropagation is one of the methods that can be implemented to perform predictions. This method performs weight and biases optimization process as parameters in backpropagation training. In this research the result value of Average Forecast Error Rate (AFER) of backpropagation method is 4.715198444% and genetic-based backpropagation method is 3.877514478%. Based on the result value of AFER, genetic-based backpropagation method can be used to predict the number of open unemployment in Indonesia with a better accuracy.